f(x) = 2x^2 - 7x + 5

we know that:

**a= 2 b = -7 c = 5**

We also know that the vertix V is:

v ( vx , vy ) such that:

vx= -b/2a

vy= - (b^2 - 4ac)/4a

Let us calculate:

vx= -b/2a = 7/2*2 = 7/4

vy...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

f(x) = 2x^2 - 7x + 5

we know that:

**a= 2 b = -7 c = 5**

We also know that the vertix V is:

v ( vx , vy ) such that:

vx= -b/2a

vy= - (b^2 - 4ac)/4a

Let us calculate:

vx= -b/2a = 7/2*2 = 7/4

vy = - (b^2 - 4ac)/4a = -(49 - 4*2*5)/4*2

= -9/8

==> vy = -9/8

Then the vertix v is:

**V ( 7/4, -9/8)**